2012
DOI: 10.1002/icd.1761
|View full text |Cite
|
Sign up to set email alerts
|

Links between Family Social Status and Preschoolers' Persistence: The Role of Maternal Values and Quality of Parenting

Abstract: Children who develop persistence in the preschool years are likely to function more effectively during the transition into school. In this study of 231 3-year-old children and their mothers, we examined the relations among family social status, maternal values of self-direction, and quality of parenting and children’s persistence in challenging tasks. Results of SEM path analysis indicated that family social status was related to maternal values of self-direction, which in turn were associated with the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
2
8
0
2
Order By: Relevance
“…Likewise, it has been established that the family's socioeconomic status predicts its disciplinary practices and children's academic success (Jansen et al, 2012;Mokrova, O'Brien, Calkins, Leerkes & Marcovitch, 2012), which supports the interviewees' beliefs about this issue. However, a recent study carried out in Chile shows no connection between low family income and parental performance (Olhaberry & Farkas, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…Likewise, it has been established that the family's socioeconomic status predicts its disciplinary practices and children's academic success (Jansen et al, 2012;Mokrova, O'Brien, Calkins, Leerkes & Marcovitch, 2012), which supports the interviewees' beliefs about this issue. However, a recent study carried out in Chile shows no connection between low family income and parental performance (Olhaberry & Farkas, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…The finding that schooling as an external factor does not seem to affect persistence leads to the hypothesis that active (adult) scaffolding behaviours, as another environmental factor, may play an especially important role for persistence development. In fact, previous research has shown that parenting qualities such as scaffolding and emotional supportive behaviour foster persistence (Lucca et al, 2019; Lunkenheimer et al, 2019; Mokrova et al, 2012; Prendergast & MacPhee, 2018). Furthermore, specific teacher behaviours such as proximity, verbal reinforcement, and the promotion of task procedures have shown to affect persistence development positively (Krantz & Scarth, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The second category focuses on external factors affecting persistence development. Parenting qualities, such as scaffolding and emotional supportive reinforcement are related to improvement in task persistence (e.g., Lunkenheimer, Panlilio, Lobo, Olson, & Hamby, 2019; Mokrova, O'Brien, Calkins, Leerkes, & Marcovitch, 2012; Prendergast & MacPhee, 2018). However, external influences are not limited to parenting qualities as such.…”
Section: Introductionmentioning
confidence: 99%
“…Remdamiesi užsienio tyrimų rezultatais, jog vaikų savireguliacijos gebėjimai yra susiję su mokytojo elgesiu klasėje, keliame prielaidą, kad sėkmingas vaikų savireguliacijos gebėjimų ugdymas gali būti susijęs ir su mokytojų saviveiksmingumo lygiu. Tyrimai rodo, kad tiek vaikų atkaklumas atliekant užduotis, tiek elgesio savireguliacija priklauso nuo vaiko lyties Son, Lee, & Sung, 2013;Pakarinen et al, 2011; ir tėvų išsilavinimo (Mokrova, O'Brien, Calkins, Leerkes, & Marcovitch, 2012;Montroy et al, 2016). Kalbant apie lytį, nustatyta, kad mergaitės yra atkaklesnės atlikdamos užduotis (Pakarinen et al, 2011) ir jų elgesio savireguliacija yra geresnė nei berniukų Son, Lee, & Sung, 2013;Von Suchodoletz & Gunzenhause, 2013).…”
unclassified
“…Šie skirtumai yra siejami su spartesne mergaičių elgesio savireguliacijos raida (Montroy et al, 2016). Kalbant apie tėvų išsilavinimą, pastebėta, kad aukštesnis tėvų išsilavinimas yra susijęs su didesniu vaikų atkaklumu atliekant užduotis (Mokrova et al, 2012) ir geresne elgesio savireguliacija (Montroy et al, 2016). Todėl analizuojant, kaip priešmokyklinio ugdymo mokytojų saviveiksmingumas prognozuoja priešmokyklinio amžiaus vaikų atkaklumą atliekant užduotis ir elgesio savireguliaciją, yra svarbu atkreipti dėmesį ir į vaikų lytį bei tėvų išsilavinimą.…”
unclassified